Expression of Tra2β in Cancer Cells as a Potential Contributory Factor to Neoplasia and Metastasis. (8th July 2013) - Best, Andrew; Dagliesh, Caroline; Ehrmann, Ingrid; Kheirollahi-Kouhestani, Mahsa; Tyson-Capper, Alison; Elliott, David J.
Abstract : The splicing regulator proteins SRSF1 (also known as ASF/SF2) and SRSF3 (also known as SRP20) belong to the SR family of proteins and can be upregulated in cancer. The SRSF1 gene itself is amplified in some cancer cells, and cancer-associated changes in the expression of MYC also increase SRSF1 gene expression. Increased concentrations of SRSF1 protein promote prooncogenic splicing patterns of a number of key regulators of cell growth. Here, we review the evidence that upregulation of the SR-related Tra2 β protein might have a similar role in cancer cells. The TRA2B gene encoding Tra2 β is amplified in particular tumours including those of the lung, ovary, cervix, stomach, head, and neck. Both TRA2B RNA and Tra2 β protein levels are upregulated in breast, cervical, ovarian, and colon cancer, and Tra2 β expression is associated with cancer cell survival. The TRA2B gene is a transcriptional target of the protooncogene ETS-1 which might cause higher levels of expression in some cancer cells which express this transcription factor. Known Tra2 β splicing targets have important roles in cancer cells, where they affect metastasis, proliferation, and cell survival. Tra2 β protein is also known to interact directly with the RBMY protein which is implicated in liver cancer.